DEVELOPMENT OF LEARNING MEDIA BASED ON ANIMATION VIDEO IN MOMENTUM AND IMPULSE TOPICS - Habib Al Husein; Togi Tampubolon (INPAFI (Inovasi Pembelajaran Fisika), 2022)
This study aims to develop momentum and impulse learning media using animated videos that are feasible to be applied as distance learning media and to find out that the development of video-based animated video learning media can support distance learning activities. This study uses a 4D (Define, Design, Develop, Disseminate) development research method with video media development using Animaker.com, Bandicam.com and Filmora. The technique of collecting data using a questionnaire / questionnaire. Define stage to determine objectives by conducting document studies. Design stage by designing until the stage of making the media. The Develop stage is to determine the feasibility assessment based on topic experts, media experts, and students. Disseminate stage by uploading videos to YouTube and in the form of CD / DVD for teachers. The feasibility of the video was based on the assessment of the topic expert with a percentage of 91% with a very feasible category, a media expert with a percentage of 79% with a very feasible category, and a student feasibility test with a percentage of 93% with a very feasible category.Keywords: Learning Media, Animated Videos.